2022
DOI: 10.1371/journal.pone.0268635
|View full text |Cite
|
Sign up to set email alerts
|

Potential of phenothiazines to synergistically block calmodulin and reactivate PP2A in cancer cells

Abstract: Phenothiazines (PTZ) were developed as inhibitors of monoamine neurotransmitter receptors, notably dopamine receptors. Because of this activity they have been used for decades as antipsychotic drugs. In addition, they possess significant anti-cancer properties and several attempts for their repurposing were made. However, their incompletely understood polypharmacology is challenging. Here we examined the potential of the PTZ fluphenazine (Flu) and its mustard derivative (Flu-M) to synergistically act on two ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Furthermore, a recent study aimed to investigate if fluphenazine and its mustard derivative ( Figure 4 ) could synergistically target two cancer-associated targets: calmodulin and the tumor suppressor protein phosphatase 2A (PP2A). These proteins are modulators of the Ras- and MAPK signaling pathways, affecting cell viability and other mechanisms related to cancer cell stemness [ 29 ]. The authors used 3D spheroids of different cell lines (breast cancer cells MDA-MB-231 (K-Ras-G13D), bronchioalveolar cancer cells NCI-H358 (K-Ras-G12C), and melanoma cells A375 (B-RAF-V600E)).…”
Section: Evidence Of Anticancer Effects Of Fluphenazine Against Diffe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent study aimed to investigate if fluphenazine and its mustard derivative ( Figure 4 ) could synergistically target two cancer-associated targets: calmodulin and the tumor suppressor protein phosphatase 2A (PP2A). These proteins are modulators of the Ras- and MAPK signaling pathways, affecting cell viability and other mechanisms related to cancer cell stemness [ 29 ]. The authors used 3D spheroids of different cell lines (breast cancer cells MDA-MB-231 (K-Ras-G13D), bronchioalveolar cancer cells NCI-H358 (K-Ras-G12C), and melanoma cells A375 (B-RAF-V600E)).…”
Section: Evidence Of Anticancer Effects Of Fluphenazine Against Diffe...mentioning
confidence: 99%
“…The authors used 3D spheroids of different cell lines (breast cancer cells MDA-MB-231 (K-Ras-G13D), bronchioalveolar cancer cells NCI-H358 (K-Ras-G12C), and melanoma cells A375 (B-RAF-V600E)). They found that the combination of fluphenazine (a calmodulin inhibitor) and DT-061 (a PP2A activator) synergistically decreased the formation of spheroids and increased apoptosis in MDA-MB-231 cells, with the mustard derivative showing a more cytotoxic potential [ 29 ]. MDA-MB-231 is a triple-negative breast cancer cell line and is representative of one of the most aggressive types of breast cancer.…”
Section: Evidence Of Anticancer Effects Of Fluphenazine Against Diffe...mentioning
confidence: 99%
“…Antipsychotic phenothiazines make up a class of drugs which are known CaM modulators [18][19][20][21]. By binding to CaM, the drugs effectively inhibit target-protein association.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Trifluoperazine (TFP, Fig 1C) is a potent member of this family of drugs whose interaction with CaM is well-studied [22][23][24][25]. Apart from antipsychotic purposes, TFP has also been investigated as treatment for various cancer forms [20]. Crystallographic structures of TFP bound to CaM revealed that the drug is capable of binding to CaM with varying stoichiometries at both inter-and intra-lobe binding sites (Fig 1D).…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…1C) is a potent member of this family of drugs whose interaction with CaM is well-studied [22][23][24][25]. Apart from antipsychotic purposes, TFP has also been investigated as treatment for various cancer forms [20]. Crystallographic structures of TFP bound to CaM revealed that the drug is capable of binding to CaM with varying stoichiometries at both interand intra-lobe binding sites (Fig.…”
Section: Introductionmentioning
confidence: 99%